Neuroplasticity. How regular physical activity influences the brain’s structure and function - Julia Dołęga; Łukasz, Stanisław Papież; Piotr Mól; Tomasz Maciejczyk; Antoni Sieńko; Małgorzata Łabuś; Bartłomiej Zabawa; Patrycja Hudzińska; Karol Krzykawski; Jakub Sadowski (Quality in Sport)
Introduction: Physical activity is associated with a reduced risk of chronic diseases, including cardiovascular disease, obesity, type 2 diabetes, and cognitive decline. Exercise supports brain health and cognitive function, with potential benefits for neuroplasticity—the brain's ability to reorganize in response to demands and injury.